If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4k + -5 = 6k + 1 Reorder the terms: -5 + 4k = 6k + 1 Reorder the terms: -5 + 4k = 1 + 6k Solving -5 + 4k = 1 + 6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6k' to each side of the equation. -5 + 4k + -6k = 1 + 6k + -6k Combine like terms: 4k + -6k = -2k -5 + -2k = 1 + 6k + -6k Combine like terms: 6k + -6k = 0 -5 + -2k = 1 + 0 -5 + -2k = 1 Add '5' to each side of the equation. -5 + 5 + -2k = 1 + 5 Combine like terms: -5 + 5 = 0 0 + -2k = 1 + 5 -2k = 1 + 5 Combine like terms: 1 + 5 = 6 -2k = 6 Divide each side by '-2'. k = -3 Simplifying k = -3
| 5(m-4)=2m+3 | | -2(z-11/5)=3z | | 2x^2-6x-9=89 | | 18=-8x+6x | | 7+6x+6x=47 | | 4x^2-16x-33=0 | | 5/6x-7/8=1/6x-1/4 | | 3/2x-(3-4x)=1/3 | | 3(3)+2(5)=60x-500 | | 5+14a=9x-5 | | 2/3×-11=14 | | -.12x^2+2.4x=8 | | y=7sinx-4 | | (x-1/3x)^2 | | 2x^3+6x^2=1 | | x=2(x+29) | | -54x=10 | | x=2x+58 | | 17x-6=10x-13 | | p=2x+58 | | 48*38= | | x=6+9 | | 7x-2-2x+5=-2x+1+6x | | 1.52=3.16(y-8.62) | | 1.52=(y-8.62) | | ydx=(3x-y^3)dy | | 6n+9=-3n-27 | | y=0.25(x-5)(x-1) | | (x)(x)+3x+2= | | ydx-(3x-y^3)dy=0 | | 2.3x+14= | | n/3=5n-42 |